Starch-based surface sizing agent as well as raw material composition, preparation method and application thereof

By developing a starch-based surface sizing agent, using specific raw material compositions and preparation methods, the problem of degradation of pulp quality caused by multiple use of waste paper is solved, and the surface strength and printing suitability of the paper are significantly improved.

CN119505093APending Publication Date: 2025-02-25SHANGHAI CHANGFA NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411676153.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the existing papermaking industry, the multiple use of waste paper leads to a decrease in the quality of the pulp, the mechanical properties of the paper are reduced, and the presence of anionic waste, which affects the printing adaptability of the paper.

Method used

A starch-based surface sizing agent is developed, and its raw material composition includes hard monomers, soft monomers, functional monomers, polyols and initiators, and the surface strength and printing suitability of the paper are improved by specific preparation methods.

Benefits of technology

It significantly improves the surface strength and printing suitability of the paper, reduces hair loss and powder loss, improves the rubber sizing and smoothness of the paper, and is suitable for pulp of different quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147096870000081
    Figure BDA0005147096870000081
  • Figure BDA0005147096870000091
    Figure BDA0005147096870000091
Patent Text Reader

Abstract

The invention discloses a starch-based surface sizing agent as well as a raw material composition, a preparation method and application thereof. The starch-based surface sizing agent comprises the following raw materials in parts by weight: 30-70 parts of a hard monomer, 20-60 parts of a soft monomer, 11-6 parts of a functional monomer, 22-10 parts of a functional monomer, 0.5-3.0 parts of an acid catalyst, 70-90 parts of native starch, 5-20 parts of polyol and 3-7 parts of an initiator. According to the invention, through the reaction of the polyhydric alcohol and the native starch, the surface strength of the raw paper can be greatly improved, meanwhile, linting and dusting are reduced, and the sizing degree, smoothness and printability of paper can be effectively improved. And during monomer graft copolymerization, functional monomers are introduced, so that the Cobb value of raw paper can be obviously improved while the cross-linking capability of the surface sizing agent and paper pulp fibers is further improved. According to the invention, modified starch is replaced by native starch, and polyhydric alcohols and functional monomers are added, so that the product can be applied to paper pulp with different qualities, and the water resistance of paper is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of papermaking chemical production, and in particular relates to a starch-based surface sizing agent, a raw material composition thereof, and a preparation method and application thereof. Background Art

[0002] The papermaking industry has become an important industry worldwide with its wide range of applications and huge market demand. Surface sizing agents, as a key link in paper production, play an important role in improving paper quality, enhancing the physical properties of the paper surface, and improving the printing adaptability of paper.

[0003] In recent years, the domestic papermaking industry has developed rapidly. With the rise in the price of pulp in the international market and the cost considerations of papermaking enterprises, the use of waste paper in terms of paper raw materials has also increased year by year. However, with the increasing number of reuses, the quality of waste paper has declined year by year. Specifically, the waste pulp fibers are short and contain many impurities. The mechanical properties of paper are greatly reduced after being made, and there are many anionic garbage in the waste paper that has been used many times. In this way, the paper and the polymer with negative charge or high anion content are not tightly combined. However, as people's requirements for paper quality continue to increase, higher requirements are put forward for papermaking surface sizing technology in terms of improving paper quality and reducing production costs. In order to cope with the current situation of reduced pulp quality in papermaking enterprises, it is urgent to develop a surface sizing agent with excellent performance suitable for pulps of different qualities. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a starch-based surface sizing agent, a raw material composition thereof, and a preparation method and application thereof.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] In one aspect, the present invention provides a raw material composition of a starch-based surface sizing agent, which comprises the following raw materials in parts by weight:

[0007] 30-70 parts of hard monomer, 20-60 parts of soft monomer, 11-6 parts of functional monomer, 22-10 parts of functional monomer, 0.5-3.0 parts of acid catalyst, 70-90 parts of native starch, 5-20 parts of polyol, and 3-7 parts of initiator.

[0008] In some embodiments, the hard monomer is at least one of styrene, α-methylstyrene, cyclohexyl methacrylate, methyl methacrylate, isobornyl methacrylate, ethyl methacrylate, isopropyl methacrylate, and vinyl acetate.

[0009] In some embodiments, the soft monomer is at least one of butyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, ethyl acrylate, and 2-hydroxypropyl acrylate.

[0010] In some embodiments, the functional monomer 1 is at least one of methylvinylchlorosilane, vinyltrichlorosilane, γ-methacryloxypropyltrimethoxysilane, perfluorohexylethyl acrylate, perfluorohexylethyl methacrylate, perfluorooctylethyl acrylate, and perfluorooctylethyl methacrylate.

[0011] In some embodiments, the functional monomer 2 is at least one of methacryloyloxyethyl trimethyl ammonium chloride, N,N-dimethylaminoethyl methacrylate, acryloyloxyethyl trimethyl ammonium chloride, N,N-dimethylaminoethyl acrylate, dimethyl diallyl ammonium chloride, and octadecyl dimethyl allyl ammonium chloride.

[0012] In some embodiments, the acidic catalyst is selected from at least one of acetic acid, hydrochloric acid, sulfuric acid, and oxalic acid.

[0013] In some embodiments, the native starch is corn starch and / or tapioca starch.

[0014] In some embodiments, the polyol is one or two of polyethylene glycol 200, polyethylene glycol 400, sorbitol, maltose syrup, pentaerythritol, xylitol, glycerol, and triglycerol.

[0015] In some embodiments, the initiator is at least one of hydrogen peroxide, dibenzoyl peroxide, potassium persulfate, tert-butyl perbenzoate, dilauroyl peroxide, ammonium persulfate, tert-butyl peroxy-2-ethylhexanoate, and sodium persulfate.

[0016] In some embodiments, the weight percentage of the hard monomer is 35 to 60 parts;

[0017] In some embodiments, the weight percentage of the soft monomer is 25 to 55 parts;

[0018] In some embodiments, the weight percentage of the functional monomer 1 is 2 to 6 parts;

[0019] In some embodiments, the weight percentage of the functional monomer 2 is 3 to 9 parts;

[0020] In some embodiments, the weight percentage of the acidic catalyst is 1 to 2.5 parts;

[0021] In some embodiments, the weight percentage of the native starch is 70 to 85 parts;

[0022] In some embodiments, the weight percentage of the polyol is 6 to 18 parts;

[0023] In some embodiments, the weight percentage of the initiator is 3.5 to 6 parts.

[0024] In some embodiments, the raw material composition of the starch-based surface sizing agent further includes deionized water; preferably, the weight proportion of the deionized water is 383 to 1026 parts.

[0025] In another aspect, the present invention provides a method for preparing a starch-based surface sizing agent, wherein the raw materials of the starch-based surface sizing agent include the raw material composition of the starch-based surface sizing agent, and specifically comprises the following steps:

[0026] (1) mixing a hard monomer, a soft monomer, a functional monomer 1 and a functional monomer 2 to prepare a material A;

[0027] (2) adding water and native starch into a reaction vessel, stirring and heating, and when the temperature reaches 40-70° C., adding an acid catalyst and a polyol to react to obtain material B;

[0028] (3) adding an initiator to the material B, and then simultaneously dropping the material A, and performing a heat-insulating reaction after the dropping is completed;

[0029] (4) After the heat preservation reaction is completed, the temperature is lowered to room temperature, and a pH regulator and deionized water are added to adjust the pH value and solid content to obtain the starch-based surface sizing agent.

[0030] In step (2), the reaction time is 1 to 6 hours;

[0031] In step (2), the reaction temperature is 40 to 70°C;

[0032] In step (3), the dropping time is 100 to 150 minutes;

[0033] In step (3), the temperature of the dropping is 80 to 100° C.;

[0034] In step (3), the temperature of the insulation reaction is 80-100° C.;

[0035] In step (3), the insulation reaction time is 30 to 90 minutes;

[0036] In step (3), the initiator is added in the form of an aqueous solution.

[0037] In step (4), after adjusting the pH value and solid content, the process also includes adding a bactericide and a defoaming agent, and filtering.

[0038] The third aspect of the present invention provides a starch-based surface sizing agent, which is prepared by the preparation method of the starch-based surface sizing agent as described above.

[0039] A fourth aspect of the present invention provides the use of a starch-based surface sizing agent in base paper surface treatment.

[0040] The beneficial effects of the present invention are:

[0041] 1. The present invention can significantly improve the surface strength of base paper by reacting polyol with native starch, reduce hair loss and powder loss, and effectively improve the sizing degree, smoothness and printability of paper. In addition, when the monomers of the present invention are grafted and copolymerized, the functional monomers are introduced to further improve the cross-linking ability of the surface sizing agent and pulp fiber, and at the same time significantly improve the Cobb value of the base paper.

[0042] 2. The present invention uses native starch instead of modified starch and adds polyols and functional monomers at the same time, so that the product can be applied to pulps of different qualities and has obvious improvements in the water resistance and surface strength of paper. DETAILED DESCRIPTION

[0043] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are selected according to conventional methods and conditions, or according to the product specifications. In addition, the reagents and raw materials used in the present invention are conventional commercial products unless otherwise specified.

[0044] Example 1

[0045] (1) 30 parts of α-methylstyrene, 60 parts of 2-hydroxyethyl acrylate, 1 part of methylvinyl chlorosilane, and 10 parts of methacryloyloxyethyl trimethylammonium chloride are mixed to obtain a mixed monomer, and 5 parts of potassium persulfate are added to 73 parts of water to prepare a solution.

[0046] (2) Add 310 parts of water and 70 parts of cassava starch into a four-necked flask and add them into a reactor. Start stirring and slowly raise the temperature. When the temperature reaches 40°C, add 3 parts of concentrated sulfuric acid and 5 parts of polyethylene glycol 200 at a time, and keep the temperature to react for 1 hour.

[0047] (3) Add the mixed monomer and initiator solution to the above-prepared material simultaneously, the dropping time is 150 min and the dropping temperature is 80°C; after the dropping is completed, keep warm at 80°C for 90 min; cool to room temperature, add acetic acid and deionized water to adjust the pH value and solid content, add bactericide and defoamer, stir evenly, filter, and obtain a surface sizing agent with pH = 2.6 and solid content = 44.8%.

[0048] Example 2

[0049] (1) 70 parts of isobornyl methacrylate, 20 parts of 2-ethylhexyl acrylate, 6 parts of perfluorohexylethyl acrylate, and 2 parts of dimethyldiallylammonium chloride are mixed to obtain a mixed monomer, and 7 parts of sodium persulfate are added to 146 parts of water to prepare a solution.

[0050] (2) Add 880 parts of water and 90 parts of corn starch into a four-necked flask and add them into a reactor. Start stirring and slowly raise the temperature. When the temperature reaches 70°C, add 0.5 parts of concentrated hydrochloric acid and 20 parts of pentaerythritol at once, and keep the temperature to react for 6 hours.

[0051] (3) Add the mixed monomer and initiator solution to the above-prepared material simultaneously, the dropping time is 100 minutes and the dropping temperature is 100°C; after the dropping is completed, keep warm at 100°C for 30 minutes; cool to room temperature, add acetic acid and deionized water to adjust the pH value and solid content, add bactericide and defoamer, stir evenly, filter, and obtain a surface sizing agent with pH = 3.8 and solid content = 20.3%.

[0052] Example 3

[0053] (1) 60 parts of vinyl acetate, 50 parts of ethyl acrylate, 4 parts of methylvinyl chlorosilane, and 5 parts of methacryloyloxyethyl trimethylammonium chloride are mixed to obtain a mixed monomer, and 6 parts of tert-butyl peroxybenzoate are added to 73 parts of water to prepare a solution.

[0054] (2) Add 580 parts of water and 80 parts of cassava starch into a four-necked flask and add them into a reactor. Start stirring and slowly raise the temperature. When the temperature reaches 50°C, add 2 parts of concentrated sulfuric acid and 14 parts of glycerol at one time, and keep the temperature to react for 5 hours.

[0055] (3) Add the mixed monomer and initiator solution to the above-prepared material simultaneously, the dropping time is 120 min and the dropping temperature is 90°C; after the dropping is completed, keep warm at 90°C for 60 min; cool to room temperature, add hydrochloric acid and deionized water to adjust the pH value and solid content, add bactericide and defoamer, stir evenly, filter, and obtain a surface sizing agent with pH = 3.2 and solid content = 31.2%.

[0056] Example 4

[0057] (1) 50 parts of vinyl acetate, 60 parts of ethyl acrylate, 5 parts of methylvinyl chlorosilane, and 7 parts of dimethyldiallylammonium chloride are mixed to obtain a mixed monomer, and 4 parts of tert-butyl peroxybenzoate are added to 146 parts of water to prepare a solution.

[0058] (2) Add 660 parts of water and 80 parts of corn starch into a four-necked flask and add them into a reactor. Start stirring and slowly raise the temperature. When the temperature reaches 60°C, add 2 parts of concentrated sulfuric acid and 10 parts of glycerol at one time, and maintain the temperature for 3 hours.

[0059] (3) Add the mixed monomer and initiator solution to the above-prepared material simultaneously, the dropping time is 130 minutes and the dropping temperature is 90°C; after the dropping is completed, keep the temperature at 90°C for 80 minutes; cool to room temperature, add sulfuric acid and deionized water to adjust the pH value and solid content, add bactericide and defoamer, stir evenly, filter, and obtain a surface sizing agent with a pH of 3.6 and a solid content of 24.6%.

[0060] Example 5

[0061] (1) 35 parts of α-methylstyrene, 25 parts of 2-hydroxyethyl acrylate, 2 parts of methylvinyl chlorosilane, and 3 parts of methacryloyloxyethyl trimethylammonium chloride are mixed to obtain a mixed monomer, and 3.5 parts of potassium persulfate are added to 73 parts of water to prepare a solution.

[0062] (2) Add 310 parts of water and 85 parts of cassava starch into a four-necked flask and add them into a reactor. Start stirring and slowly raise the temperature. When the temperature reaches 40°C, add 1 part of concentrated sulfuric acid and 6 parts of polyethylene glycol 200 at a time, and keep the temperature to react for 1 hour.

[0063] (3) The same as step (3) of Example 1, the surface sizing agent obtained, pH = 2.8, solid content = 43.6%

[0064] Example 6

[0065] (1) 35 parts of α-methylstyrene, 55 parts of 2-hydroxyethyl acrylate, 2 parts of methylvinyl chlorosilane, and 9 parts of methacryloyloxyethyl trimethylammonium chloride are mixed to obtain a mixed monomer, and 3 parts of potassium persulfate are added to 73 parts of water to prepare a solution.

[0066] (2) Add 310 parts of water and 85 parts of cassava starch into a four-necked flask and add them into a reactor. Start stirring and slowly raise the temperature. When the temperature reaches 40°C, add 2.5 parts of concentrated sulfuric acid and 18 parts of polyethylene glycol 200 at one time, and keep the temperature to react for 1 hour.

[0067] (3) The same as step (3) of Example 1, the surface sizing agent obtained has a pH of 45.5 and a solid content of 3.1%.

[0068] Comparative Example 1

[0069] The sizing agent prepared according to the method of Example 4 of Chinese patent CN201110026816.8 has a solid content of 15%.

[0070] Comparative Example 2

[0071] The only difference from Example 1 is that the dropping time of step (3) is 90 min.

[0072] Comparative Example 3

[0073] The only difference from Example 1 is that the reaction temperature in step (2) is 80°C.

[0074] Comparative Example 4

[0075] The only difference from Example 1 is that the amount of raw material cassava native starch is different, which is 50 parts.

[0076] Comparative Example 5

[0077] The only difference from Example 1 is that the raw material polyethylene glycol 200 is replaced by ethylene glycol.

[0078] Effect Example

[0079] 1. Cobb value determination: Use XSH Cobb absorbency tester produced by Hangzhou Qingtong Bo Ke Automation Technology Co., Ltd. to test the paper sample according to GB / T 1540-1989 method.

[0080] 2. Surface strength measurement: measured using J-IGT350 IGT printing adaptability instrument.

[0081] 3. Surface sizing on offset paper: Use the sizing solution prepared in Comparative Examples 1 to 5 and Examples 1 to 6 on offset paper with a coating amount of 1.8 g / m 2 After coating, bake in an oven at 110°C for 30 seconds or 120 seconds, take out, cool to room temperature and then measure.

[0082] Process 1: dilute the sizing agents prepared in the formulations of Comparative Examples 2 to 5 and Examples 1 to 6 with deionized water to 15 wt %.

[0083] Preparation of sizing solution: prepare 500 g of 10 wt% oxidized starch aqueous solution, heat to 90°C, gelatinize for 20 minutes, cool to 40°C, add sizing agent prepared by the formula of comparative examples 1 to 5 and embodiments 1 to 6 (oxidized starch (dry): sizing agent (wet) = 50:2), and then dilute with water to 8 wt%.

[0084] Judgment criteria: The smaller the Cobb value, the better; the greater the surface strength, the better. The measurement results are shown in Table 1.

[0085] Table 1

[0086]

[0087] Process 2: dilute the sizing agents prepared in the formulations of Comparative Examples 2 to 5 and Examples 1 to 6 with deionized water to 15 wt %.

[0088] Preparation of sizing solution: prepare 500 g of 10 wt% oxidized starch aqueous solution, heat to 90°C, gelatinize for 20 minutes, cool to 40°C, add sizing agent prepared by the formula of comparative examples 1 to 5 and embodiments 1 to 6 (oxidized starch (dry): sizing agent (wet) = 50:3), and then dilute with water to 8 wt%.

[0089] The measurement results are shown in Table 2.

[0090] Table 2

[0091]

[0092] It can be seen from the above application results that the sizing agents prepared by Examples 1 to 6 of the present invention can not only significantly improve the Cobb value, but also greatly improve the surface strength of the base paper and reduce hair loss and powder loss compared with Comparative Examples 1 to 5.

[0093] Finally, it should be noted that in the present invention, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method, article or apparatus.

[0094] Although the present disclosure has been disclosed above through the description of the specific embodiments of the present disclosure, it should be understood that those skilled in the art can design various modifications, improvements or equivalents to the present disclosure within the spirit and scope of the attached scheme. These modifications, improvements or equivalents should also be considered to be included in the scope of protection claimed by the present disclosure.

Claims

1. A raw material composition of a starch-based surface sizing agent, characterized in that: It contains the following raw materials in parts by weight: 30-70 parts of hard monomer, 20-60 parts of soft monomer, 11-6 parts of functional monomer, 22-10 parts of functional monomer, 0.5-3.0 parts of acid catalyst, 70-90 parts of native starch, 5-20 parts of polyol, and 3-7 parts of initiator.

2. The raw material composition of the starch-based surface sizing agent according to claim 1, characterized in that: The hard monomer is at least one of styrene, α-methylstyrene, cyclohexyl methacrylate, methyl methacrylate, isobornyl methacrylate, ethyl methacrylate, isopropyl methacrylate, and vinyl acetate; And / or, the soft monomer is at least one of butyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, 2-hydroxyethyl acrylate, ethyl acrylate, and 2-hydroxypropyl acrylate; And / or, the functional monomer 1 is at least one of methylvinylchlorosilane, vinyltrichlorosilane, γ-methacryloxypropyltrimethoxysilane, perfluorohexylethyl acrylate, perfluorohexylethyl methacrylate, perfluorooctylethyl acrylate, and perfluorooctylethyl methacrylate; And / or, the functional monomer 2 is at least one of methacryloyloxyethyl trimethyl ammonium chloride, N,N-dimethylaminoethyl methacrylate, acryloyloxyethyl trimethyl ammonium chloride, N,N-dimethylaminoethyl acrylate, dimethyl diallyl ammonium chloride, and octadecyl dimethyl allyl ammonium chloride; And / or, the acidic catalyst is selected from at least one of acetic acid, hydrochloric acid, sulfuric acid, and oxalic acid; And / or, the native starch is corn starch and / or cassava starch; And / or, the polyol is one or two of polyethylene glycol 200, polyethylene glycol 400, sorbitol, maltose syrup, pentaerythritol, xylitol, glycerol, and triglycerol; And / or, the initiator is at least one of hydrogen peroxide, dibenzoyl peroxide, potassium persulfate, tert-butyl perbenzoate, dilauroyl peroxide, ammonium persulfate, tert-butyl peroxy-2-ethylhexanoate, and sodium persulfate.

3. The raw material composition of the starch-based surface sizing agent according to claim 1, characterized in that: The weight proportion of the hard monomer is 35 to 60 parts; And / or, the weight proportion of the soft monomer is 25 to 55 parts; And / or, the weight proportion of the functional monomer 1 is 2 to 6 parts; And / or, the weight proportion of the functional monomer 2 is 3 to 9 parts; And / or, the weight portion of the acidic catalyst is 1 to 2.5 parts; And / or, the weight proportion of the native starch is 70 to 85 parts; And / or, the weight proportion of the polyol is 6 to 18 parts; And / or, the weight proportion of the initiator is 3.5 to 6 parts.

4. The raw material composition of the starch-based surface sizing agent according to any one of claims 1, characterized in that: The raw material composition of the starch-based surface sizing agent further includes deionized water; preferably, the weight proportion of the deionized water is 383 to 1026 parts.

5. A method for preparing a starch-based surface sizing agent, characterized in that: The raw material of the starch-based surface sizing agent comprises the raw material composition of the starch-based surface sizing agent according to any one of claims 1 to 4, and specifically comprises the following steps: (1) mixing a hard monomer, a soft monomer, a functional monomer 1 and a functional monomer 2 to obtain a material A; (2) adding water and native starch into a reaction vessel, stirring and heating, and when the temperature reaches 40-70° C., adding an acid catalyst and a polyol to react to obtain material B; (3) adding an initiator to the material B, and then simultaneously dropping the material A, and performing a heat-insulating reaction after the dropping is completed; (4) After the heat preservation reaction is completed, the temperature is lowered to room temperature, and a pH regulator and deionized water are added to adjust the pH value and solid content to obtain the starch-based surface sizing agent.

6. The method for preparing a starch-based surface sizing agent according to claim 5, characterized in that: The preparation method satisfies at least one of the following conditions: In step (2), the reaction time is 1 to 6 hours; In step (2), the reaction temperature is 40 to 70°C; In step (3), the dropping time is 100 to 150 minutes; In step (3), the temperature of the dropping is 80 to 100° C.; In step (3), the temperature of the insulation reaction is 80-100° C.; In step (3), the insulation reaction time is 30 to 90 minutes.

7. The method for preparing a starch-based surface sizing agent according to claim 5, characterized in that: In step (3), the initiator is added in the form of an aqueous solution.

8. The method for preparing a starch-based surface sizing agent according to claim 5, characterized in that: In step (4), after adjusting the pH value and solid content, the process also includes adding a bactericide and a defoaming agent, and filtering.

9. A starch-based surface sizing agent, characterized in that: The sizing agent is prepared by the method for preparing the starch-based surface sizing agent according to any one of claims 5 to 8.

10. Use of the starch-based surface sizing agent according to claim 9 in surface treatment of base paper.

Citation Information

Patent Citations

  • Novel cationic surface sizing agent and preparation method thereof

    CN102140768B

Cited By

  • High-acid-value reactive polycarboxylic acid, high-carboxyl fiber synergistic composition for electrostatic base paper and application of high-carboxyl fiber synergistic composition and surface sizing

    CN122257295A